Pelaksanaan Pembelajaran Daring Seni Budaya Di SMP Negeri 17 Padang - Ayu Nurhasanah; Erfan Erfan (FBS Universitas Negeri Padang, 2020)
This study aims to describe online instruction of Culture and Arts especially in Music subject matter in class VII.5 at SMP Negeri 17 Padang. This is a qualitative research using a descriptive analytic approach. The research instrument used was the researcher itself and was assisted by supporting instruments such as writing tools, cameras, and cellphones. The data were collected through literature study, interviews, and documentation.Based on the results of the study, it can be concluded that the implementation ofonline instructionin the subject matter of simple musical instruments in class VII.5 at SMP Negeri 17 Padang is using the Whatsapp Group media recommended by the Principal of SMP Negeri 17 Padang. This is a way to deal with online learning so that learning activities can be continued even though it is conducted in distance. The planning step for learning simple musical instrument is not optimally conducteddue to the fact that the teacher does not create lesson plans for online instruction.The implementation of online learning in the subject matter of simple musical instrumentcontinues to run smoothly even though the learning process faces various obstacles. The learning outcomes of Culture and Arts for grade VIIin the subject matter of simple musical instruments are less effective and less optimal. This is due to the fact that learning activities conducted do not pay attention to standards of preparing online learning materials.